2019
DOI: 10.1142/s1793962319500211
|View full text |Cite
|
Sign up to set email alerts
|

Financial risk assessment model based on big data

Abstract: Conventional financial risk assessment is not accurate and its adaptive assessment ability is low. In order to solve this problem, a financial risk assessment model based on big data is proposed. In this method, the quantitative analysis method is adopted to analyze the explanatory variable model and the control variable model of financial risk assessment. The market-to-book ratio, asset–liability ratio, cash flow ratio and financing structure model are adopted as constraint parameters to construct a big data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In order to solve this problem, he proposed a big data-based financial risk assessment model, which uses regression analysis to conduct big data analysis and prediction of financial risk assessment. Although the scholar's point of view is very good, he did not use some practical examples to illustrate whether the model he established is feasible [1]. Zhu and Liu found that establishing a good financial risk early warning mechanism has become very meaningful in today's society.…”
Section: Related Workmentioning
confidence: 99%
“…In order to solve this problem, he proposed a big data-based financial risk assessment model, which uses regression analysis to conduct big data analysis and prediction of financial risk assessment. Although the scholar's point of view is very good, he did not use some practical examples to illustrate whether the model he established is feasible [1]. Zhu and Liu found that establishing a good financial risk early warning mechanism has become very meaningful in today's society.…”
Section: Related Workmentioning
confidence: 99%
“…is method uses quantitative analysis methods to analyze the explanatory variable model and the controlled variable model of financial risk assessment. e simulation results show that this method can provide high financial risk assessment accuracy; it has a strong adaptive evaluation ability for risk coefficients, and it has good application value in the prevention and control of financial system risk factors [2]. Zhai et al proposed a multiattention fusion modeling (multi-AFM) to address the problems of low efficiency and heavy workload of university curriculum evaluation methods.…”
Section: Related Workmentioning
confidence: 99%
“…e calculation of the above formula needs to first calculate the partial derivatives z/zT (h) nm y(t, c, a, b) and z/zc (h) n y(t, c, a, b) of the cost function y(t, c, a, b) corresponding to a single training sample (a, b), and the BP algorithm is very effective for calculating the partial derivative of the cost function [2]. e entire process of the back propagation algorithm is as follows:…”
Section: Back Propagation Algorithmmentioning
confidence: 99%
“…Based on the economic game theory, big data technology is used to predict the possible risks in the financial field. Finally, an adaptive financial risk assessment scheme is formed [ 6 ]. His research is both theoretically and methodologically good, but no applied analysis of actual data has been carried out, and its predictive effect needs to be further verified.…”
Section: Introductionmentioning
confidence: 99%